Parental Insight and Action: Exploring the Link Between Knowledge and Early Childhood Dental Caries Prevention in Sukoharjo, Central Java, Indonesia - Firmansyah, Gusti Fathoni; Pamungkasari, Eti Poncorini; Widyaningsih , Vitri (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2025)
Background: The most common case of dental and oral diseases suffered by early childhood is dental caries, dental caries can be prevented, one of which is by modifying the thoughts, lifestyle, and daily habits of the parents. One of the models that can be used to change dental caries prevention behavior is by using the Health Belief Model (HBM). The purpose of this study is to identify factors such as vulnerability perception, seriousness perception, benefit perception, obstacle perception, motivation to act and parental self-efficacy towards dental caries prevention behavior in early childhood in Sukoharjo Regency. Subject and Method: This study was conducted using a quantitative approach with an analytical observational research method with a cross-sectional research design. The sample amounted to 111 parents from children aged 6 to 8 years in Weru District, Sukoharjo Regency with the Multistage Cluster Random Sampling technique. This study uses primary data sources with data collection techniques through questionnaires and then multivariate analysis with multiple linear regression methods. The content of the questionnaire includes behavior to prevent dental caries in children based on parental perception and parental knowledge about dental caries prevention based on the Health Belief Model (HBM) construct. Results: There was a positive association of vulnerability perception (b=0.16; CI 95%= 0.01 to 0.17; p=0.024), perception of seriousness (b=0.16; CI 95%= 0.01 to 0.19; p=0.050), perception of benefits (b=0.173; CI 95%= 0.005 to 0.21; p=0.040), action signal (b=0.21; CI 95%= 0.01 to 0.27; p=0.036), and self-efficacy (b=0.19; CI 95%= 0.01 to 0.21; p=0.037) on the behavior of preventing dental caries in children, and there was a negative relationship between the perception of obstacles (b=0.15; CI 95%= 0.01 to 0.13; p=0.047) on the behavior of preventing dental caries in children. Conclusion: Perception of vulnerability, perception of seriousness, perception of benefit, action cues, and parental self-efficacy have a positive effect on dental caries prevention behavior in children. On the other hand, the perception of obstacles from parents has a negative effect on dental caries prevention behavior in children.